This is not a food magazine - Ng, Sheere (Singapore; In Plain Words; Temporary Press, 2023)
A collection of essays and articles about culture and identity in Singapore through the lens of food. This compilation contains contents ranging from Zi Char menus, Home Economics curriculums, unassuming kitchen/cooking tools critical for making signature dishes, to contemplations on specific local food or recipes. There is also interesting relationships between its contents and design with many insights that might remain unnoticed if not for the author$1 (Bs versatile and broad range of interests and inquiry.A collection of essays and articles about culture and identity in Singapore through the lens of food. This compilation contains contents ranging from Zi Char menus, Home Economics curriculums, unassuming kitchen/cooking tools critical for making signature dishes, to contemplations on specific local food or recipes. There is also interesting relationships between its contents and design with many insights that might remain unnoticed if not for the author$1 (Bs versatile and broad range of interests and inquiry.s
English
Keywords: N4390-5098 Visual Arts. Exhibitions; Singapore